Extracellular Nucleic Acids - Kikuchi, Yo.; Kikuchi, Yo.; Rykova, Elena Y.; Rykova, Elena Y. (Nucleic Acids and Molecular Biology,, 2010)
Extracellular nucleic acids have recently emerged as important players in the fields of biology and the medical sciences. In the last several years, extracellular nucleic acids have been shown to be involved in not only microbial evolution as genetic elements but also to have structural roles in bacterial communities, such as biofilms. Circulating DNA and RNA have been found in human blood and expected to be useful as non-invasive markers for the diagnosis of several diseases. In addition, extracellular nucleic acids have attracted attention as active modulators of the immune system of higher organisms, including humans. This book covers nearly all of the newly developing fields related to extracellular nucleic acids, including those of basic biology, ecology and the medical sciences, and provides readers with the latest knowledge on them.